MICROENCAPSULATION OF PROBIOTICS BY EXTRUSION METHOD ASSOCIATED WITH ELECTROSTATIC INTERACTIONS - Etchepare, Mariana Araújo (2015)
Probiotics are live microorganisms that when consumed in adeequadas amounts confer a number of benefits for the health of the host due to improved intestinal microflora. Bacteria of the genus Lactobacillus, Bifidobacterium, and Bacillus have been widely studied and are added to various food types. However, the physicochemical stability and bioavailability of these bacteria have represented a major challenge for the food industry, especially in non-refrigerated food products. The microencapsulation helps to improve the survival of these bacteria, it protects the microorganisms from adverse conditions such as high and low temperatures, pH, additives, or during processing and its passage through the gastrointestinal tract. Most flooring materials used in the carrier to microncapsulação probiotic foods are ionic microbial polysaccharides, exopolysaccharides, and milk proteins, which exhibit different physicochemical characteristics. The preparation of microcapsules results from numerous techniques available, each with its particularity. Among the microencapsulation techniques probiotics, extrusion is most popularly employed for obtaining microparticles. In this review, will be addressed topics regarding microencapsulation of probiotics by extrusion method associated with electrostatic interactions to develop microcapsules with potential application in foods.